Надійність інтегрованої звітності - Сокіл, Олег Григорійович; Сокол, Олег Григорьевич; Sokil, Oleh (My University, 2019)
UK: В даній статті представлені висновки з аналізу надійності інтегрованої звітності в світлі стратегічної та інформаційної парадигми бухгалтерського обліку. Дослідження демонструє надійність в світлі міжнародних стандартів, які стандартизують інтегровану звітність, відповідно до якої існує необхідність в підвищенні довіри. В якості ключової форми підвищення надійності інтегрованої звітності автор вказує на внутрішню і зовнішню перевірку фінансових даних і їх розкриття, які засновані на звіті про управління, пов'язаному з відповідальністю підприємства. Мета дослідження була досягнута шляхом використання відповідних методів дослідження, включаючи, зокрема, критичний аналіз наукової літератури і метод аналогій. Дослідження носить аксіоматичний характер і ґрунтується на припущеннях фундаментальної теорії інституту бухгалтерського обліку. EN: The purpose of the article is to study the need and options for ensuring the relia-bility of integrated reporting using the methods of the Institute of Accounting. Research results. This paper presents the conclusions from analyzing the reliability of integrated reporting in the light of the strategic and information-related paradigm of accounting. The study demonstrates the reliability in the light of international standards that standardize integrated reporting, according to which there is a need for the improvement of credibility. As a key form of improving the reliability of integrated reporting the author indicates an internal and external verification of financial data and non-financial disclosure, both based on accountability ac-count related to a company’s responsibility. The purpose of the study was achieved by employing pertinent research methods, including in particular a critical analysis of scholarly literature and the method of analogy. The study is axiomatic in nature, based on fundamental accounting theory assumptions. Conclusions. Given the growing demand for information, it is expected that the sustainable development accounting system will be a proper tool for measuring asset value, capital and performance. Therefore, one of the key conditions for the development of integrated reporting by increasing its reliability is the development of verification and validation system and their adaptation to the needs that contribute to sustainable development.
The reliability of integrated reporting
Keywords: облік соціальної відповідальності; інтегрована звітність; валідація; верифікація; social responsibility; accounting; integrated reporting; validation; verification